DESERTIFICATION SUSCEPTIBILITY OF GILBUÉS (PIAUÍ STATE) AND CABROBÓ (PERNAMBUCO STATE) DRYLANDS, IN NORTHEASTERN BRAZIL - Sheydder-de-O-Lopes, Laryssa; Celestino-Soares, Rafael (Revista Geográfica de América Central., 2016)
Desertification is a process of weakness of the drylands ecosystems in general that, due to the excessive pressure from human populations, loses its productivity and capacity to regenerate itself. The objective of this study was to discuss the susceptibility to desertification in two pilot areas in Northeastern Brazil: Gilbués (Piauí State) and Cabrobó (Pernambuco State). These areas have differentiated characteristics of geology, soil, climate and vegetation. However, human activities have points in common, such as agriculture, deforestation and livestock. The methodology was the literature review and field research to collect data and photographic records. The consequences of desertification result in the local population impoverishment and loss of environmental quality, as well as in regional migration processes, loss of biodiversity and territory.